The Effect of Environmental Performance and CEO Gender on Carbon Emission Disclosure in the Basic Materials Sector Listed on the Indonesia Stock Exchange for the 2022 - 2024 Period - Nadia Saputri; Mella A Listia (Yayasan Az Zukhruf Cendikia, 2026)
Abstract Purpose – This study aims to obtain empirical evidence on the effect of environmental performance and CEO gender on carbon emission disclosure. Design/methodology/approach – This study uses quantitative research. The sample in this study consists of 66 companies in the basic materials sector listed on the Indonesia Stock Exchange from 2022 - 2024. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews9 software. Findings –The results of this study indicate that the environmental performance variable has a positive and is statistically insignificant effect on carbon emissions disclosure. The CEO gender variable has a positive and is statistically insignificant effect on carbon emissions disclosure. These findings suggest that improving environmental performance and CEO gender differences are not sufficient to significantly encourage carbon emission conservation practices, which are largely voluntary in Indonesia. Research limitations/implications – his study aims to provide practical empowerment for regulators such as the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX), highlighting the need for more standardized and mandatory carbon emission regulations, particularly for environmentally sensitive sectors. It also provides information on carbon emission distribution that can be useful in decision-making and serve as a reference for further research. JEL : Q56, M14, and G34